2022
DOI: 10.1039/d2ta04466h
|View full text |Cite
|
Sign up to set email alerts
|

Towards understanding the nucleation and growth mechanism of Li dendrites on zinc oxide-coated nickel electrodes

Abstract: While lithium metal is considered an ideal anode for the next generation of high-energy-density batteries, some major issues such as huge volume change and continuous dendrite formation during lithium plating...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…A recent trend in recent papers has been to modify current collectors to improve lithium nucleation and growth behavior. ,, Previously we have shown that the use of ZnO-coated Ni foam leads to the formation of a lower surface area lithium and overall leads to better electrochemical performance . Yet, achieving maximum electrochemical performance requires the optimization of the ZnO layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…A recent trend in recent papers has been to modify current collectors to improve lithium nucleation and growth behavior. ,, Previously we have shown that the use of ZnO-coated Ni foam leads to the formation of a lower surface area lithium and overall leads to better electrochemical performance . Yet, achieving maximum electrochemical performance requires the optimization of the ZnO layer thickness.…”
Section: Resultsmentioning
confidence: 99%
“…It has been revealed that zinc prefers to deposit on the sites with lower surface energy during the zinc deposition process, which leads to the formation of needle-like dendrites [13]. Consequently, there is a higher electric field at the tip of the zinc dendrite due to the modulation of the electric field on the uneven surface of the zinc foil disc [14]. As shown in Figure 1a, zinc dendrites are gradually extended towards the cathode materials and eventually lead to a short-circuit.…”
Section: Introductionmentioning
confidence: 99%
“…22,28 Meanwhile, the lithiophilic ZnO facilitates the uniform Li nucleation and increases the lateral Li atom diffusion rate. [29][30][31] Due to the synergistic effect between BP and ZnO, uniform Li deposition is achieved. Consequently, Li metal anodes with the ZnO@BP nanosheet coating (ZnO@BP/Li) exhibit enhanced interface kinetics and excellent cycling performances in symmetric cells.…”
Section: Introductionmentioning
confidence: 99%